Impacts of the Coronavirus on Brazilian Agribusiness and its Relationship with the Gross Domestic Product (Global Journal of Management and Business Research, 2024)
The objective of this study was to identify the consequences of the pandemic on Brazilian agribusiness and its relationship with the Gross Domestic Product GDP Through an analysis of spreadsheets published by CEPEA and through a study of the indebtedness and profitability indicators of eighteen companies in the agribusiness sector listed in the non-cyclical consumption sector of B3 S A The collection of the financial data of the companies was through the Econometrics database The research is characterized as descriptive with a documentary procedure the longitudinal cut of data analysis was carried out between 2019 and 2020 as it was the time frame with the greatest impact that the pandemic brought to the indicators as for the approach it is characterized as quantitative To establish the relationship between the economic index GDP and the economic-financial indicators of agribusiness companies the research used Pearson s Correlation as a statistical tool The study findings indicate that 89 of agribusiness companies increased their revenues in the year of the pandemic through the demand for agricultural commodities A rise in the value added of the sector was evidenced by the insertion of new international markets favored by the increase in the dollar
Keywords: pandemic; agribusiness; indicators